ONLINE PSYCHOEDUCATION ABOUT THE DANGERS OF EARLY MARRIAGE AGAINST THE HIGH INCIDENCE OF DIVORCE DURING THE PANDEMIC - Yulianti Yulianti (Universitas Muhammadiyah Ponorogo, 2022)
The phenomenon of early marriage occurs at the national and international levels. According to Riskesdas data, the number of married girls aged 15-19 years is more signify (11.7%) companion male adolescents aged 15-19 years at 1.6% (Anwar Rahmah, 2016). Child marriage is related to various factors that can be structural or originate from the community, family, or individual capacity.The purpose of this study was to determine the effect of online psychoeducation on increasing the knowledge of Regina Celli Metland High School students about the dangers of early marriage. This study uses the Pre Experimental method with a one-group pre-test design. The sampling technique used was total sampling with a total sample of 53 respondents. Data analysis using Paired T-Test and Logistics Regression Test. The results showed that the P-value 0.000 0.05, which means that there are differences in the use of online psychoeducation methods with audiovisual video media to increase the knowledge of Regina Celli Metland High School students. The conclusion of the study states that online psychoeducation can increase the knowledge of Regina Celli Metland High School students about the dangers of early marriage.